2009
DOI: 10.1111/j.1749-6632.2009.04787.x
|View full text |Cite
|
Sign up to set email alerts
|

Memory for Tonal Pitches

Abstract: One of the most studied effects of verbal working memory (WM) is the influence of the length of the words that compose the list to be remembered. This work aims to investigate the nature of musical WM by replicating the word length effect in the musical domain. Length and rate of presentation were manipulated in a recognition task of tone sequences. Results showed significant effects for both factors (length and presentation rate) as well as their interaction, suggesting the existence of different strategies (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…More complex melodies are likely to place higher demands on the limited capacity of working memory, resulting in lower memorability. There are several different ways of operationalizing melodic complexity; previous studies have used the number of notes in the melody (Akiva-Kabiri, Vecchi, Granot, Basso, & Schön, 2009;Brittin, 2000;DeWitt & Crowder, 1986;Edworthy, 1985;Schulze et al, 2012), and some studies have also used contour complexity (Croonen, 1994;. While high length is reliably associated with poor melody discrimination performance, the effect of contour complexity seems less reliable.…”
Section: Memory Retentionmentioning
confidence: 99%
See 1 more Smart Citation
“…More complex melodies are likely to place higher demands on the limited capacity of working memory, resulting in lower memorability. There are several different ways of operationalizing melodic complexity; previous studies have used the number of notes in the melody (Akiva-Kabiri, Vecchi, Granot, Basso, & Schön, 2009;Brittin, 2000;DeWitt & Crowder, 1986;Edworthy, 1985;Schulze et al, 2012), and some studies have also used contour complexity (Croonen, 1994;. While high length is reliably associated with poor melody discrimination performance, the effect of contour complexity seems less reliable.…”
Section: Memory Retentionmentioning
confidence: 99%
“…Akiva-Kabiri et al, 2009;DeWitt & Crowder, 1986;Schulze et al, 2012). In this paper we use the number of notes in the melody as well as two additional measures of melodic complexity.…”
Section: Melodic Complexitymentioning
confidence: 99%
“…Over four different blocks, we manipulated tone duration (100 ms, 350 ms) and ITI (present or absent), which also resulted in changes in stimulus onset asynchrony (SOA, corresponding to the sum of tone duration and ITI). It has been demonstrated that short-term memory abilities decrease with increasing memory load for auditory and visual modalities 18 27 32 . We thus manipulated the sequence length (three or four tones) to test whether the benefits of an increased time to encode tone sequences can be observed in particular when the task difficulty increased.…”
mentioning
confidence: 99%
“…All melodies produced by Racchman-Oct2010 were subsequently filtered to ensure that they contained no out-of-key notes, and transposed to the key of D major. For manipulating item difficulty we varied item length based on evidence showing that longer melodies are harder to encode (Brittin, 2000 ; Akiva-Kabiri et al, 2009 ). Five different levels of melody length were therefore employed, staggered in logarithmic steps (lengths of 6, 7, 9, 12, 16 notes).…”
Section: Methodsmentioning
confidence: 99%